Identification of 3-hydroxy-1, 2-dimethylpyridine-4(1H)-thione as a metal-binding motif for the inhibition of botulinum neurotoxin A. Issue 1 (12th November 2020) - Lin, Lucy; Turner, Lewis D.; Šilhár, Peter; Pellett, Sabine; Johnson, Eric A.; Janda, Kim D.
Abstract : The 3, 4-HOPTO pharmacophore was identified as an inhibitor of botulinum neurotoxin A light chain. Structure-activity relationships were explored, resulting in a compound that protects SNAP-25 cleavage in motor neurons. Abstract : Botulinum neurotoxin serotype A (BoNT/A) is an important therapeutic target owing to its extremely potent nature, but also has potential use as a biowarfare agent. Currently, no therapeutic exists to reverse the long-lasting paralysis caused by BoNT/A. Herein, we describe the identification of 3-hydroxy-1, 2-dimethylpyridine-4(1 H )-thione (3, 4-HOPTO) as a metal binding warhead for the inhibition of BoNT/A1. An initial screen of 96 metal binding fragments identified three derivatives containing the 3, 4-HOPTO scaffold to inhibit the BoNT/A1 light chain (LC) at >95% at 1 mM. Additional screening of a 3, 4-HOPTO sub-library identified structure–activity relationships (SARs) between N -substituted 3, 4-HOPTO derivatives and the BoNT/A1 LC. Subsequent synthesis was conducted to improve on inhibitory potency – achieving low μM biochemical IC50 values. Representative compounds were evaluated in a cellular-based assay and showed promising μM activity.